1995
DOI: 10.1002/jnr.490410107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of proteoglycan expression in developing chicken brain: Characterization of a heparan sulfate proteoglycan that interacts with the neural cell adhesion molecule

Abstract: In the present study we have characterized the major proteoglycans of chick brain, focusing on their pattern of expression in development and on identifying the heparan sulfate proteoglycan (HSPG) that binds to the neural cell adhesion molecule (NCAM). The major chondroitin sulfate proteoglycans (CSPG) are a heterogeneous group of molecules with an average MW of 450 kDa. Protein core analysis reveals multiple protein cores between 100 and 350 kDa. The HSPGs are somewhat smaller, with an average MW of 350 kDa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 69 publications
0
34
1
Order By: Relevance
“…5a), we assessed whether NCAM expressed on target cells might indirectly exert its inhibitory effect on NK lysis by cis-association with sulfated proteoglycans. 48,49 Our results clearly showed that inhibition of NK lysis was independent of the presence of heparan sulfate, as NCAM transfection of pgsA-745 and CHO-K1 equally reduced the lysis by polyclonal NK cells (Figs. 5b and 5c).…”
Section: Resultsmentioning
confidence: 57%
“…5a), we assessed whether NCAM expressed on target cells might indirectly exert its inhibitory effect on NK lysis by cis-association with sulfated proteoglycans. 48,49 Our results clearly showed that inhibition of NK lysis was independent of the presence of heparan sulfate, as NCAM transfection of pgsA-745 and CHO-K1 equally reduced the lysis by polyclonal NK cells (Figs. 5b and 5c).…”
Section: Resultsmentioning
confidence: 57%
“…However the large width of the synaptic cleft and the interposition of a basal lamina would seem to preclude such homophilic interactions across postnatal NMJs. It seems more likely that NCAM, which postnatally becomes concentrated both prejunctionally and postjunctionally (Covault and Sanes, 1986), would interact heterophilically with other molecules in the synaptic basal lamina, such as neural agrin (Ferns et al, 1993), to which it can bind (Burg et al, 1995). NCAM might also interact with other molecules enriched in synaptic regions including synaptic laminins (Sanes et al, 1990;Patton et al, 1997;Sanes and Lichtman, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The HSPG nature of agrin was independently confirmed in two independent studies showing that agrin, when expressed in its entirety, carries heparan sulfate side chains , and showing that a HSPG isolated from bovine kidney comprised agrin-like peptide sequences (Hagen et al, 1993). Brain-derived agrin has also been shown to bind to NCAM via its heparan sulfate side chains, and to promote cell adhesion as an NCAM/ agrin complex (Burg et al, 1995).…”
Section: Indexing Terms: Proteoglycan; Extracellular Matrix; Axonal Gmentioning
confidence: 98%